Needs Analysis of Instructional Materials for English Speaking Skills for Nursing Students at STIKES Toraja - Nehru P. Pongsapan (LPPM UKI Toraja, 2017)
Developing teaching material is the process of selecting, adapting and evaluating of teaching based on specific terms of reference. Need Analysis is very important before designing teaching materials for English for Specific Purpose. The study aims at exploring the learning needs of 60 nursing students and 5 lecturers at STIKES Toraja, and 14 nurses who some of them work in a hospital for English speaking community such as INCO/VALE HOSPITAL Sorowako and ELIM RANTEPAO HOSPITAL Tana Toraja, South Sulawesi Indonesia. and developing ESP materials for nurses based on Need Analysis. Need Analysis in this study is categorized as Target situation Analysis, Present Situation Analysis, Deficiency Analysis, Strategy Analysis, Constraint Analysis, Pedagogic Need Analysis, and Subjective Need Analysis. The study uses quantitative and qualitative methods. The findings describe the real needs of students of ESP for nurses, the lecturers’ view points on the practice of ESP instructions, and descriptions of ESP for nurses used in English speaking countries or English speaking community. The results are very significant for designers developers of ESP of various fields for they reflect the real needs of nursing students. It is suggested that Nursing English textbooks should be based on the Need Analysis by ESP designers and developers.